2022
DOI: 10.1002/ctm2.725
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase 1 regulatory inhibitor subunit 14C promotes triple‐negative breast cancer progression via sustaining inactive glycogen synthase kinase 3 beta

Abstract: Triple‐negative breast cancer (TNBC) is fast‐growing and highly metastatic with the poorest prognosis among the breast cancer subtypes. Inactivation of glycogen synthase kinase 3 beta (GSK3β) plays a vital role in the aggressiveness of TNBC; however, the underlying mechanism for sustained GSK3β inhibition remains largely unknown. Here, we find that protein phosphatase 1 regulatory inhibitor subunit 14C (PPP1R14C) is upregulated in TNBC and relevant to poor prognosis in patients. Overexpression of PPP1R14C faci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…On the contrary, in the work of Horvath et al, a very low density of "expressed" SNPs was demonstrated in the chr2 region:48000000-48999999 containing the genes PPP1R21, MSH6, FBX011, FOXN2, STON1, GTF2A1L, and LHCGR in patients with all three analyzed BC subtypes (TNBC, non-TNBC, and HER2 positive) [70]. There is evidence of an association of increased expression of another representative of phosphoprotein phosphatase 1-PPP1R14C, with an increased risk of development and a poor prognosis (metastasis) with the TNBC variant of BC [71].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, in the work of Horvath et al, a very low density of "expressed" SNPs was demonstrated in the chr2 region:48000000-48999999 containing the genes PPP1R21, MSH6, FBX011, FOXN2, STON1, GTF2A1L, and LHCGR in patients with all three analyzed BC subtypes (TNBC, non-TNBC, and HER2 positive) [70]. There is evidence of an association of increased expression of another representative of phosphoprotein phosphatase 1-PPP1R14C, with an increased risk of development and a poor prognosis (metastasis) with the TNBC variant of BC [71].…”
Section: Discussionmentioning
confidence: 99%
“…We performed functional annotation of these significant SNPs and found that four of them are located within genes, including 1:15865487, 2:1502986, and 2:1787269. PPP1R14C is a phosphatase reported to be a major regulator of glycogen synthase kinase 3β (GSK 3β), which is involved in glycogen synthesis and storage [24]. The expression of tyrosine hydroxylase (TH) in the gastrointestinal tract affects glucose homeostasis [25].…”
Section: Discussionmentioning
confidence: 99%
“…SOX4 is a transcription factor with increased expression in a number of malignancies where its expression is positively correlated with increased cell proliferation, inhibition of apoptosis, and tumor progression [76]. Two genes upregulated in tumors from all races and with a role in tumorigenesis were PPP1R14C, which was shown to promote breast cancer cell proliferation, maintaining GSK3 in an inactive state in triple-negative breast cancer [77], and EGFL6, which regulates angiogenesis and tumor growth [78,79]. Two of the genes we confirmed by qPCR showed a race-dependent decrease in expression, including DAB2 and CAV2.…”
Section: Discussionmentioning
confidence: 99%